The impact of a shade from the growth and the results of two varieties soybean ( glycine max l .Merrill ) superior nationa - mia herisva; Taufan Hidayat; Zaitun Zaitun (Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Abstract. Soybean needs national until now as still filled with than the import value that production in the country not enough. In solve the problems the low rate production soybean required production techniques of technology and awareness nice about the cultivation of plants soybean , the expansion of the increase , fix the quality , the environment and the use of varieties superior. Efforts to improving production soybean bounded by the limited by land ownership because some rice-fields productive have changed to a non farming. Behind the limited resources land for the expansion of the acreage of a farm, there are land potential to to use, namely land under kanofi plantation crops. The purpose of this study is to find the impact of shade and varieties and interaction between them to growth and the production of the soybean plant. Design experiments used in this research is a swath separate ( RPT) with two factors treatment. The research results show that treatment shade very had have real impact on some parameters that observed , on the parameter tall plant , diameter of the stem , flowering age , age harvest , the number of pods total , the number of pods pithy , heavy seeds 100 points and potential the results , the best result in find in treatment nuangan 60 % . Varieties influential very real to pertumbuhandan production the soybean plant, based on the results of observation tall plant, diameter of the stem, flowering age, the use of varieties anjasmoro showed growth and best in compared with varieties ringing. There are the interaction that very real between shade and varietas.kombinasi that tends to both in find in varieties anjasmoro but shade 60 %